Solar repowering of PCC-retrofitted power plants; solar thermal plant dynamic modelling and control strategies. (September 2015) - Parvareh, Forough; Milani, Dia; Sharma, Manish; Chiesa, Matteo; Abbas, Ali
Highlights: Model superstructure of a PCC-retrofitted power plant with solar thermal plant. Control and operation schemes identified and analysed under dynamic conditions. Surplus power produced from solar repowering matches PCC reboiler decline in power plant output. Enhanced flexibility in power plant dispatch with reduced emissions. Abstract: Solar repowering of high pressure side feed water preheaters of post combustion carbon capture (PCC) retrofitted power plants offers a promising capability to offset the power plant output penalty due to capture plant reboiler duty. In this work, a model based approach is used to investigate the technical, operational and control aspects of the solar thermal installation of the super structure (power plant + PCC + solar thermal plant). The base case is a 660 MWe PCC-retrofitted power plant operating at 100% capacity and 90% capture rate in Australia. This is repowered by a solar thermal plant consisting of (a) a parabolic trough solar collector field with 806, 520 m 2 aperture area, (b) a thermal storage system with 8 full load hours of thermal storage and (c) an auxiliary gas heating unit, ensuring the solar thermal plant provides the high pressure side feed water preheating duty at all times without requirement to withdraw any steam from the power plant turbine circuit. A total of 230 MWth is provided from the solar thermal plant installation, being 100% supply for high pressure and intermediate feed water preheaters duty plus a surplus of 30% for maintaining the deaerator operation. A key feature here is trying to eliminate the frequent changes to the steam flow rate in the turbine circuit for solar feed water preheating and thus promoting ease of retrofit of repowering technology to PCC-retrofitted power plants. Details of the component sizing and modelling of solar thermal installation are provided and control and operating schemes are identified and analysed. A comprehensive dynamic model in TRNSYS dynamic modelling software is developed and used to analyse the solar thermal plant dynamic responses to external disturbances including climatic changes (Typical Meteorological data for Sydney is used). The analysis limitations and capabilities are highlighted. The model performance for month December is assessed showing its full capability to track the changes from power plant duty requirement and meteorological data within the time lapse of 0.01 s.